2013
DOI: 10.13172/2053-2636-1-1-957
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and risk factors for non-alcoholic fatty liver disease (NAFLD) in community-dwellers of Beijing, China

Abstract: These findings need to be confirmed in prospective studies and randomised controlled trials designed to further clarify the pathogenesis of non-alcoholic fatty liver disease and to establish evidence-based dietary recommendations for its prevention and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The prevalence of NAFLD in the general population ranges from 6.3% to 51% depending on the method used to assess liver steatosis and the population/ethnicity studied [41][42][43][44][45]. This prevalence can be significantly higher in individuals with MRFs [46][47][48].…”
Section: Commentsmentioning
confidence: 99%
“…The prevalence of NAFLD in the general population ranges from 6.3% to 51% depending on the method used to assess liver steatosis and the population/ethnicity studied [41][42][43][44][45]. This prevalence can be significantly higher in individuals with MRFs [46][47][48].…”
Section: Commentsmentioning
confidence: 99%
“…In western China, where the majority of ethnic minorities live, the prevalence of MAFLD ranges from 21.8 to 26.1% [ 5 , 6 ]. Of note, during the last decade, the prevalence of MAFLD in this region has doubled according to previous studies [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 79%
“…Waist circumference is almost same in both males and females and the values are 95.21±11.17 cms , 95.11±11.38 cms respectively. Research study conducted by G Li etal found that NAFLD group had significantly larger proportion of males (63.6%) and the mean body mass index (BMI) was 23.7 ± 3.3 kg /m2, and the mean of waist circumferences (WC) was 79.9 ± 10.1 c m 17 . It was high in both males and females of our study.…”
Section: Discussionmentioning
confidence: 99%